Nuclear and Electron Spin Resonance Studies on Skyrmion‐Hosting Lacunar Spinels. Issue 5 (5th November 2021) - Prinz-Zwick, Markus; Szigeti, Bertalan G.; Gimpel, Thomas; Ehlers, Dieter; Tsurkan, Vladimir; Leonov, Andrey O.; Miksch, Björn; Scheffler, Marc; Stasinopoulos, Ioannis; Grundler, Dirk; Kézsmárki, István; Büttgen, Norbert; et al.
Abstract : Magnetic resonance techniques at nuclei and electrons are applied to characterize the electronic structure and collective magnetic excitations throughout the magnetic phase diagrams of the lacunar spinels GaV4 S8 and GaV4 Se8 showing cycloidal, Néel‐type skyrmion lattice and ferromagnetically polarized phases. 71 Ga nuclear magnetic resonance (NMR) provides a local probe of the rhombohedral distortion and the resulting uniaxial magnetic anisotropy via the detection of electric field gradients (EFGs) and hyperfine coupling at the gallium sites of these lacunar spinels. Broadband electron spin resonance (ESR) allows identifying clockwise, counterclockwise, and breathing modes of the skyrmion‐lattice phase supported by theoretical simulations. Abstract : Magnetic resonance is applied to characterize the electronic structure and collective magnetic excitations of the lacunar spinels GaV4 S8 and GaV4 Se8 showing cycloidal, Néel‐type skyrmion lattice (SkL), and ferromagnetic phases. 71 Ga nuclear magnetic resonance provides a local probe of the rhombohedral distortion and uniaxial magnetic anisotropy. Broadband electron spin resonance allows identifying clockwise, counterclockwise, and breathing modes of the SkLs.